Electrolyte, lithium ion battery and electric equipment

By using aminoborane and/or its derivatives as film forming additives in the lithium-ion battery electrolyte, a low impedance and high temperature stability SEI film and CEI film are generated, which solves the problem of insufficient performance of batteries under high temperature conditions in the prior art, and achieves better high temperature cycling performance and power performance.

CN119764560AActive Publication Date: 2025-04-04CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410356081.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2025-04-04
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

Existing film-forming additives cannot take into account the low impedance and good high-temperature stability of the SEI film and CEI film of lithium-ion batteries, resulting in insufficient cycling and power performance of the battery under high temperature conditions.

Method used

The dense SEI film and CEI film are used as film forming additives by electrochemical reactions on the electrode surface to improve their low impedance and high temperature stability.

Benefits of technology

The generated SEI film and CEI film have low impedance and high temperature stability, which improves the high temperature cycling and power performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764560A_ABST
    Figure CN119764560A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses an electrolyte, a lithium ion battery and electric equipment, the electrolyte comprises a film-forming additive, the film-forming additive comprises amino borane and / or an amino borane metal derivative, the chemical formula of the amino borane metal derivative is M (NH2BH3) n, M is metal, and n is a positive integer equal to the chemical valence state of M. The film-forming additive has high reduction potential and low oxidation potential, electrochemical reaction can be carried out on the surfaces of a positive electrode and a negative electrode to generate a compact SEI film and a compact CEI film, the generated SEI film and the generated CEI film have the characteristics of low impedance and good high-temperature stability, and the high-temperature cycle performance and the power performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an electrolyte, a lithium ion battery and an electrical device. Background Art

[0002] Lithium-ion batteries are widely used in mobile electronic devices, electric vehicles, energy storage systems and other fields due to their high energy density and low pollution. During the first cycle of charge and discharge of lithium-ion batteries, the electrolyte undergoes side reactions on the surface of the electrode material, forming a SEI (Solid Electrolyte Interphase) film at the negative electrode and a CEI (Chemical-Electrochemical Interface) film at the positive electrode. The SEI film and CEI film can prevent electron transmission and allow lithium ion transmission, thereby inhibiting the electrolyte from corroding the electrode material and the occurrence of side reactions. The lithium ion conductivity and high-temperature stability of the SEI film and CEI film determine the interface performance of the electrode-electrolyte. In order to meet the battery's requirements for high energy density, long life, and high power, it is necessary to form a SEI film and CEI film with low impedance and good high-temperature stability.

[0003] At present, the electrode interface performance is improved by adding film-forming additives to the battery electrolyte. However, the existing film-forming additives have relatively single functions. For example, the commonly used negative electrode film-forming additive vinyl carbonate can improve the high-temperature stability of the electrode, but the SEI film formed has a large impedance and cannot take into account the power performance. The SEI film formed by fluoroethylene carbonate and vinyl sulfate has low impedance and good power performance, but insufficient high-temperature stability and serious gas production. Therefore, it is necessary to provide a film-forming additive that can reduce the impedance of the SEI film and CEI film and improve its high-temperature stability. Summary of the invention

[0004] Based on this, an embodiment of the present invention provides an electrolyte containing a film-forming additive. The film-forming additive has a high reduction potential and a low oxidation potential, and can undergo electrochemical reactions on the surfaces of the positive and negative electrodes to generate dense SEI films and CEI films. The generated SEI films and CEI films have the characteristics of low impedance and good high-temperature stability, which is beneficial to improving the high-temperature cycle performance and power performance of the battery.

[0005] In a first aspect, an embodiment of the present invention provides an electrolyte, comprising a film-forming additive, wherein the film-forming additive comprises aminoborane and / or an aminoborane derivative; the aminoborane derivative comprises an aminoborane metal derivative, and the chemical formula of the aminoborane metal derivative is M(NH2BH3), wherein M is a metal and n is a positive integer equal to the chemical valence state of M.

[0006] In an embodiment of the present invention, M is selected from Li, Na, K, Mg, Ca, and Al.

[0007] In an embodiment of the present invention, the aminoborane metal derivative includes at least one of LiNH2BH3, NaNH2BH3, KNH2BH3, Mg(NH2BH3)2, Ca(NH2BH3)2 and Al(NH2BH3)3.

[0008] In an embodiment of the present invention, the mass percentage of the aminoborane and / or aminoborane derivative in the electrolyte is 0.1%-10%.

[0009] In an embodiment of the present invention, the electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate and lithium perchlorate.

[0010] In an embodiment of the present invention, the molar concentration of the lithium salt in the electrolyte is 0.1 mol / L-5 mol / L.

[0011] In an embodiment of the present invention, the electrolyte further comprises a solvent, and the solvent comprises at least one of a carbonate solvent, a carboxylate solvent and an ether solvent.

[0012] In an embodiment of the present invention, the mass percentage of the solvent in the electrolyte is 10%-90%.

[0013] The electrolyte provided by the embodiment of the present invention contains a film-forming additive. The film-forming additive has a higher reduction potential and a lower oxidation potential than the commonly used electrolyte solvent. During the first charge and discharge process, the SEI film and the CEI film can be generated before the electrolyte solvent on the surface of the positive and negative electrodes by electrochemical reaction, thereby inhibiting the consumption of the solvent. The SEI film and the CEI film formed by the film-forming additive are rich in Li3N and LiF inorganic components, with high lithium ion conductivity and low impedance, which is conducive to improving the rate performance of the battery. On the other hand, they are rich in [LiNBH] n Organic components such as polymer chains have strong toughness and help alleviate the volume expansion of electrode materials during the charging and discharging process, especially the expansion of electrodes under high temperature conditions, which is beneficial to improving the high-temperature cycle stability of the battery.

[0014] In a second aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the electrolyte described in the first aspect.

[0015] The lithium-ion battery provided by the embodiment of the present invention contains a film-forming additive, which can form a SEI film and a CEI film with low impedance and good high-temperature stability, can improve the stability of the battery electrode interface, and help improve the high-temperature cycle stability and power performance of the battery.

[0016] In a third aspect, an embodiment of the present invention provides an electrical device, wherein the electrical device comprises the lithium-ion battery described in the second aspect.

[0017] The electric device provided in the embodiment of the present invention comprises the lithium-ion battery of the second aspect, and the lithium-ion battery has good high-temperature stability and power performance, so that the electric device can be used stably for a long time, which is beneficial to improving the performance of the electric device. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the accompanying drawings required for use in the embodiment of the present invention will be described below.

[0019] Figure 1 is a schematic structural diagram of a lithium-ion battery 100 in one embodiment of the present invention;

[0020] Figure 2 1 is a cyclic voltammetry curve of the button cell provided in Example 3 of the present invention and Comparative Example 1;

[0021] Figure 3 It is a linear sweep voltammetry curve diagram of the button-type half-cell provided in Example 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] At present, lithium-ion batteries mainly face challenges such as capacity decay, slow charging, low safety and high cost. In order to solve these problems, lithium-ion batteries are gradually developing towards high specific energy and long life, which requires the selection of electrode materials to tend to high voltage platforms or high specific capacity electrode materials. As the voltage increases, the side reactions of traditional electrolytes and electrode materials also increase. The products formed while consuming more active lithium will cause the SEI film to thicken, the impedance to increase, and the capacity to decay. Therefore, the stability of the electrode-electrolyte interface of lithium-ion batteries directly affects the various electrochemical properties and safety of the battery.

[0024] In order to improve the battery electrode-electrolyte interface performance, the most commonly used method is to add film-forming additives to the battery electrolyte. The film-forming additives can form stable and effective SEI films and CEI films on the surface of the electrode material. The SEI film and CEI film allow lithium ions to freely enter and exit the electrode while maintaining good electronic insulation properties, preventing the electrode material from further reacting with the electrolyte, and maintaining the stability of the structure, thereby reducing the first irreversible capacity loss of the lithium-ion battery and improving the battery's rate performance and cycle life. However, the existing film-forming additives have the defect of not being able to take into account both high-temperature cycle stability and power performance. For example, the commonly used film-forming additive vinyl carbonate can improve the high-temperature stability of the electrode, but the SEI film formed has a large impedance and cannot take into account the power performance. The SEI film formed by fluoroethylene carbonate and vinyl sulfate has low impedance and good power performance, but insufficient high-temperature stability and serious gas production. Therefore, it is necessary to provide a film-forming additive that can both reduce the impedance of the SEI film and the CEI film and improve its high-temperature stability.

[0025] Based on this, an embodiment of the present invention provides an electrolyte, the electrolyte includes a film-forming additive, and the film-forming additive includes aminoborane and / or an aminoborane derivative. In an embodiment of the present invention, the aminoborane derivative includes at least one of an aminoborane metal derivative and an aminoborane alkyl derivative.

[0026] In the embodiment of the present invention, the chemical formula of the aminoborane metal derivative is M(NH2BH3) n , wherein M is a metal and n is a positive integer. In an embodiment of the present invention, M may be selected from Li, Na, K, Mg, Ca, and Al. The present application can further ensure that the relative proportion of the effective ingredient aminoborane in the aminoborane metal derivative is relatively large by selecting an aminoborane metal derivative containing a metal element with a relatively small element mass, and further improve the film-forming performance of the film-forming additive. In some embodiments of the present invention, the aminoborane metal derivative may be at least one of LiNH2BH3, NaNH2BH3, KNH2BH3, Mg(NH2BH3)2, Ca(NH2BH3)2, and Al(NH2BH3)3, and the above-mentioned aminoborane metal derivatives are easy to obtain, which is conducive to cost control. In some embodiments of the present invention, the aminoborane alkyl derivative may be, for example, ethylenediamine diborane (EDAB), diethylenetriamine triborane (DETAB), triethylenetetramine tetraborane (TETAB), and tetraethylenepentamine pentaborane (TEPAB).

[0027] The electrolyte provided by the embodiment of the present invention contains a film-forming additive. The film-forming additive has a higher reduction potential and a lower oxidation potential than the commonly used electrolyte solvent. It can undergo electrochemical oxidation and reduction reactions on the electrode surface before the electrolyte solvent to generate a dense SEI film and CEI film, thereby inhibiting the consumption of the solvent. At the same time, the generated SEI film and CEI film have the characteristics of low impedance and good high-temperature stability, which is beneficial to improving the high-temperature cycle performance and power performance of the battery. Specifically, firstly, the film-forming additive contains abundant boron-nitrogen bonds in its molecules, which can weaken the Li + The solvation between solvent molecules can promote the + The desolvation process is beneficial to improve the diffusion kinetics of lithium ions in the electrolyte, thereby improving the power performance of the battery. Secondly, the film-forming additive can adjust the solvation sheath by forming anion-rich solvation structure. Due to the presence of boron-nitrogen bonds, Li + The anion content in the first solute sheath increases, which promotes the decomposition of anions during the charge and discharge cycle, thereby forming an anion-derived SEI film rich in Li3N and LiF. The ionic conductivity of Li3N and LiF is high, which is conducive to the transfer of lithium ions. Therefore, the Li + Enhanced conductivity can reduce battery impedance, increase battery charging speed and efficiency, and thus improve battery power performance. Furthermore, the film-forming additive will form [LiNBH]n polymer chains during the film-forming process. This polymer can enhance the toughness of the SEI film and alleviate the expansion of the negative electrode material during the charging and discharging process, especially the expansion under high temperature conditions, thereby enhancing the high-temperature stability of the SEI film and thus improving the high-temperature cycle performance of the battery. At the same time, the film-forming additive will also form a layer rich in Li3N, LiF and boron-nitrogen bonds ((NH=BH)) during the film-forming process on the positive electrode surface. n ) of the CEI membrane, these components have high ionic conductivity and good high temperature stability, which makes the CEI membrane have good high temperature stability and low impedance, thereby improving the high temperature cycle performance and power performance of the battery.

[0028] In an embodiment of the present invention, the mass percentage of aminoborane and / or aminoborane derivatives in the electrolyte can be 0.1%-10%, which can effectively improve the stability of SEI film and CEI film, reduce its impedance to improve the interface performance of electrode-electrolyte, take into account the specific capacity of the electrolyte, and avoid the waste of film-forming additives, which is conducive to cost control. In some embodiments, the mass percentage of aminoborane and / or aminoborane derivatives in the electrolyte can be, for example, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.3%, 2.6%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.3%, 4.5%, 5%, 6%, 7%, 8%, 9% or 10%. In some embodiments of the present application, the film-forming additive includes aminoborane, and the mass percentage of aminoborane in the electrolyte is 0.1%-10%. In some embodiments of the present application, the film-forming additive includes an aminoborane derivative, and the mass percentage of the aminoborane derivative in the electrolyte is 0.1%-10%. In some embodiments of the present application, the film-forming additive includes aminoborane and an aminoborane derivative, and the total mass percentage of the aminoborane and the aminoborane derivative in the electrolyte is 0.1%-10%.

[0029] In an embodiment of the present invention, the film-forming additive may further include at least one of an unsaturated ester additive and a sulfur-containing additive. The aminoborane and the aminoborane metal derivatives used in combination with the above additives can synergistically improve the interface performance of the electrode and better balance the high temperature stability and power performance of the battery. Specifically, the unsaturated ester additive may be, for example, one or more of vinylene carbonate, fluoroethylene carbonate, and vinyl ethylene carbonate; the sulfur-containing additive may be, for example, one or more of 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, vinyl sulfate, vinyl sulfite, and propylene sulfite.

[0030] In an embodiment of the present invention, the electrolyte further comprises a lithium salt. In the present invention, the main function of the lithium salt is to provide lithium ions to ensure that the battery has sufficient lithium ions during the charge and discharge process, and these lithium ions are transmitted between the positive and negative electrodes, and are embedded and de-embedded in the negative electrode material during the charge and discharge process. In some embodiments, the lithium salt may be, for example, at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium trifluoromethylsulfonate (LiOTf), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF4) and lithium perchlorate (LiClO4).

[0031] In an embodiment of the present invention, the molar concentration of the lithium salt in the electrolyte may be 0.1 mol / L-5 mol / L, which can ensure the conductivity and ion transfer rate of the battery, avoid waste of lithium salt, and help control costs. In some embodiments, the molar concentration of the lithium salt in the electrolyte may be, for example, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L or 5 mol / L.

[0032] In an embodiment of the present invention, the electrolyte further comprises a solvent, and the function of the solvent is to effectively dissolve the lithium salt so that the ions between the positive and negative electrodes can move freely, thereby realizing the flow of current. In some embodiments, the solvent comprises at least one of a carbonate solvent, a carboxylate solvent, and an ether solvent. Specifically, the carbonate solvent may be a cyclic or chain carbonate and its derivatives, for example, it may be one or more of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, propyl acetate, ethyl propionate and ethyl butyrate; the carboxylate solvent may be a linear or branched carboxylate and its derivatives, for example, it may be one or more of γ-butyrolactone, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate and ethyl butyrate; the ether solvent may be one or more of ethylene glycol ether solvents, diethylene glycol ether solvents, triethylene glycol ether solvents and tetraethylene glycol ether solvents, for example, it may be one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

[0033] In an embodiment of the present invention, the mass percentage of the solvent in the electrolyte may be 10%-90%, which can not only dissolve the lithium salt well, but also avoid the waste of the solvent, which is beneficial to control the cost. In some embodiments, the mass percentage of the solvent in the electrolyte may be, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%.

[0034] The embodiment of the present invention further provides a lithium-ion battery, which includes the electrolyte in any of the above embodiments. Specifically, the lithium-ion battery can be composed of a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, wherein the electrolyte includes the electrolyte in any of the above embodiments. The lithium-ion battery provided by the embodiment of the present invention contains a film-forming additive, which can form a SEI film and a CEI film with low impedance and good high-temperature stability, which can improve the stability of the battery electrode interface and help improve the high-temperature cycle stability and power performance of the battery.

[0035] In a specific embodiment, Figure 1As shown, the lithium-ion battery 100 includes a negative electrode 10, an electrolyte 20, a separator 30, a positive electrode 40 and a battery case 50, wherein the electrolyte 20 and the separator 30 are located between the negative electrode 10 and the positive electrode 40, and the battery case 50 is used to encapsulate the negative electrode 10, the electrolyte 20, the separator 30 and the positive electrode 40.

[0036] In an embodiment of the present invention, the positive electrode 40 may include a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the negative electrode 10 may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the positive electrode active material layer may include a positive electrode active material, a conductive agent and a binder, and the negative electrode active material layer may include a negative electrode active material, a conductive agent and a binder. The present application does not specifically limit these materials, and appropriate materials may be selected according to actual application requirements.

[0037] In an embodiment of the present invention, the positive electrode current collector may be aluminum foil; and the negative electrode current collector may be copper foil.

[0038] In an embodiment of the present invention, the positive electrode active material may be a phosphate positive electrode active material or a ternary positive electrode active material. Specifically, the positive electrode active material may be one or more of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium vanadium phosphate fluorophosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide; the negative electrode active material may be one or more of graphite material, hard carbon material, soft carbon material, silicon-based material, and tin-based material.

[0039] In an embodiment of the present invention, the conductive agent may be one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes. In some embodiments, the mass percentage of the conductive agent in the positive electrode active material layer may be 1%-4%, and the mass percentage of the conductive agent in the negative electrode active material layer may be 1%-4%.

[0040] In an embodiment of the present invention, the binder may be one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives. In some embodiments, the mass percentage of the binder in the positive electrode active material layer may be 1%-5%, and the mass percentage of the binder in the negative electrode active material layer may be 1%-5%.

[0041] In the embodiment of the present invention, the separator may be a polypropylene film (PP), a polyethylene film (PE) or a PP / PE composite film.

[0042] The embodiment of the present invention further provides an electric device, which includes the lithium-ion battery in any of the above embodiments. Specifically, the electric device can be an electric car, an electric motorcycle, an electric bicycle, a mobile power supply, an unmanned aerial vehicle, a mobile phone, a computer, a camera, an electric tool, a smart home or a wearable device.

[0043] The electric device provided in the embodiment of the present invention comprises a lithium-ion battery, which has good high-temperature stability and power performance, so that the electric device can be used stably for a long time, which is beneficial to improving the performance of the electric device.

[0044] The technical solution of the present invention is further illustrated below through specific embodiments and comparative examples.

[0045] Example 1

[0046] (1) Preparation of electrolyte

[0047] In a glove box filled with argon, ethylene carbonate (EC), diethyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:1:1, and then lithium hexafluorophosphate (LiPF6) is added to prepare an electrolyte base liquid. Then, a film-forming additive aminoborane is added to the electrolyte base liquid to obtain an electrolyte, in which the LiPF6 concentration is 1 mol / L and the mass percentage of aminoborane is 0.1%.

[0048] (2) Preparation of batteries

[0049] Preparation of negative electrode sheet: Graphite, conductive carbon black (Super P), thickener sodium carboxymethyl cellulose (CMC) and adhesive styrene-butadiene rubber (SBR) are mixed into a slurry at a mass ratio of 50:1:1:1.5, and evenly coated on the copper foil as the negative electrode current collector, dried at 85°C under vacuum for 24 hours, and then cold pressed, and then trimmed, cut, and striped, and then dried at 110°C under vacuum for 4 hours, and the tabs are welded to make negative electrode sheets;

[0050] Preparation of positive electrode sheet: lithium cobalt oxide LiCoO2 (LCO), conductive agent conductive carbon black (Super P) and adhesive polyvinylidene fluoride (PVDF) are mixed into a uniform positive electrode slurry at a mass ratio of 50:1:1, and evenly coated on aluminum foil as a positive electrode current collector, dried at 80°C under vacuum for 24 hours, and then cold pressed, and then trimmed, cut, and striped, and then dried at 110°C under vacuum for 4 hours, and the tabs are welded to make positive electrode sheets;

[0051] Preparation of soft-pack batteries: The prepared positive and negative electrodes and separators are wound to obtain LCO / graphite soft-pack batteries. In an argon glove box with a water content of less than 5 ppm, the prepared electrolyte is injected into the soft-pack battery with an airbag, left to stand for 24 hours, and then a cycle test is performed;

[0052] Preparation of button cells: Assemble the prepared negative electrode sheet, lithium sheet, electrolyte and separator into a CR2016 button cell for testing the reduction potential of the electrolyte. Use stainless steel sheets to assemble the lithium sheet into a button half-cell for testing the oxidation potential of the electrolyte;

[0053] Formation process: The whole battery is first charged to 1.9V at 0.05C current and maintained at 1.9V for 10 hours to fully wet the battery electrode sheet. After the constant voltage is completed, the battery is initially charged at a smaller current of 0.01C for 10 hours to form a stable and dense SEI film, then charged to 4.4V at 0.05C current, and finally discharged to 2.75V.

[0054] Example 2

[0055] (1) Preparation of electrolyte

[0056] The difference from Example 1 is that the mass percentage of aminoborane in the electrolyte is 0.5%.

[0057] (2) Preparation of batteries

[0058] Same as Example 1.

[0059] Example 3

[0060] (1) Preparation of electrolyte

[0061] The difference from Example 1 is that the mass percentage of aminoborane in the electrolyte is 1%.

[0062] (2) Preparation of batteries

[0063] Same as Example 1.

[0064] Example 4

[0065] (1) Preparation of electrolyte

[0066] The difference from Example 1 is that the mass percentage of aminoborane in the electrolyte is 2%.

[0067] (2) Preparation of batteries

[0068] Same as Example 1.

[0069] Example 5

[0070] (1) Preparation of electrolyte

[0071] The difference from Example 1 is that the mass percentage of aminoborane in the electrolyte is 5%.

[0072] (2) Preparation of batteries

[0073] Same as Example 1.

[0074] Example 6

[0075] (1) Preparation of electrolyte

[0076] The difference from Example 1 is that the mass percentage of aminoborane in the electrolyte is 10%.

[0077] (2) Preparation of batteries

[0078] Same as Example 1.

[0079] Example 7

[0080] (1) Preparation of electrolyte

[0081] The difference from Example 1 is that amino borane is replaced by lithium amino borane LiNH2BH3, and the mass percentage of lithium amino borane in the electrolyte is 2%.

[0082] (2) Preparation of batteries

[0083] Same as Example 1.

[0084] Example 8

[0085] (1) Preparation of electrolyte

[0086] The difference from Example 1 is that amino borane is replaced by sodium ammonia borane NaNH2BH3, and the mass percentage of sodium ammonia borane in the electrolyte is 2%.

[0087] (2) Preparation of batteries

[0088] Same as Example 1.

[0089] Example 9

[0090] The difference from Example 1 is that amino borane is replaced by magnesium ammonia borane Mg(NH2BH3)2, and the mass percentage of magnesium ammonia borane in the electrolyte is 2%.

[0091] (2) Preparation of batteries

[0092] Same as Example 1.

[0093] Example 10

[0094] The difference from Example 1 is that aminoborane is replaced by aluminum ammonia borane Al(NH2BH3)3, and the mass percentage of aluminum ammonia borane in the electrolyte is 2%.

[0095] (2) Preparation of batteries

[0096] Same as Example 1.

[0097] Comparative Example 1

[0098] (1) Preparation of electrolyte

[0099] The difference from Example 1 is that the electrolyte does not contain aminoborane.

[0100] (2) Preparation of batteries

[0101] Same as Example 1.

[0102] Comparative Example 2

[0103] (1) Preparation of electrolyte

[0104] The difference from Example 1 is that aminoborane is replaced by vinylene carbonate (VC), and the mass percentage of vinylene carbonate (VC) in the electrolyte is 2%.

[0105] (2) Preparation of batteries

[0106] Same as Example 1.

[0107] Comparative Example 3

[0108] (1) Preparation of electrolyte

[0109] The difference from Example 1 is that aminoborane is replaced by 1,3-propane sultone (PS), and the mass percentage of 1,3-propane sultone (PS) in the electrolyte is 2%.

[0110] (2) Preparation of batteries

[0111] Same as Example 1.

[0112] The electrolytes, soft-pack batteries and button batteries of Examples 1-10 and Comparative Examples 1-3 were subjected to the following performance tests:

[0113] (1) Reduction-oxidation potential test

[0114] The button cells of the embodiment and comparative example were subjected to cyclic voltammetry test, with a scan rate of 0.2 mV / s and a scan range of 0.005 V to 3 V. The reduction potential test results of the electrolyte obtained are shown in Table 1. The cyclic voltammetry test results of the button cells of embodiment 3 and comparative example 1 are shown in Table 1. Figure 2 As shown. Figure 2 It can be seen that the aminoborane in the electrolyte of Example 3 has a reduction peak at about 1.36 V, while the carbonate solvent in the electrolyte of Comparative Example 1 has a reduction peak at about 0.8 V, indicating that the reduction potential of aminoborane is higher than that of the carbonate solvent.

[0115] The button-type half-cells of the embodiment and the comparative example were subjected to a linear sweep voltammetry test at a scan rate of 0.2 mV / s and a scan range of 3.0 V to 6 V. The test results of the oxidation potential of the electrolyte obtained are shown in Table 1. The linear sweep voltammetry test results of the button-type half-cells of the embodiment 3 and the comparative example 1 are shown in Table 1. Figure 3 As shown. Figure 3 It can be seen that the aminoborane in the electrolyte of Example 3 has an oxidation peak at 4.0 V, while the carbonate solvent in the electrolyte of Comparative Example 1 has an oxidation peak at 4.5 V, indicating that the oxidation potential of aminoborane is lower than that of the carbonate solvent.

[0116] Table 1 Reduction potential and oxidation potential of the electrolytes of Examples 1-10 and Comparative Examples 1-3

[0117] Group <![CDATA[Reduction potential (vs. Li + / Li, V)]]> <![CDATA[Oxidation potential (vs. Li + / Li, V)]]> Example 1 1.36 4.01 Example 2 1.37 4.01 Example 3 1.36 4.01 Example 4 1.36 4.0 Example 5 1.34 3.99 Example 6 1.34 3.99 Example 7 1.41 4.03 Example 8 1.38 4.02 Example 9 1.38 4.05 Example 10 1.38 4.05 Comparative Example 1 0.8 4.5 Comparative Example 2 1.1 4.25 Comparative Example 3 1.2 4.1

[0118] As can be seen from Table 1, the reduction potential of the film-forming additive provided in the embodiment of the present invention to lithium is between 1.34V and 1.41V, which is higher than the reduction potential of the carbonate solvent, and the oxidation potential is between 3.99V and 4.05V, which is lower than the oxidation potential of the carbonate solvent. Therefore, the film-forming additive provided in the embodiment of the present invention can preferentially oxidize and reduce the carbonate solvent to form the SEI film and the CEI film, thereby protecting the solvent and reducing the solvent consumption.

[0119] (2) High temperature cycle test

[0120] The soft pack batteries of the embodiment and the comparative example (10 batteries for each condition, the results are averaged) were cycled 200 times at 1C current between 2.75V and 4.4V. The high temperature cycle test was carried out in a 45°C constant temperature box. The capacity retention rate (%) was calculated as the percentage obtained by dividing the discharge capacity at the 200th cycle by the initial discharge capacity of the first cycle. The test results of the high temperature cycle experiment are shown in Table 2.

[0121] (3) Battery impedance test

[0122] The soft-pack batteries of the embodiment and the comparative example (10 batteries for each condition, the results are averaged) were cycled 120 times at 500 mA (1C) between 2.75 V and 4.5 V, and the AC impedance was measured at -10°C after the batteries were discharged to 2.75 V. The low-temperature AC impedance test results are shown in Table 2.

[0123] Table 2 High temperature cycle test and low temperature AC impedance test results

[0124]

[0125] As can be seen from Table 2, the capacity retention rates of the soft-pack batteries of Examples 1-10 at high temperatures are all higher than those of Comparative Example 1, indicating that the film-forming additives provided in the embodiments of the present invention can effectively improve the high-temperature cycle performance of the battery. It can also be seen from Table 2 that the AC impedances of the soft-pack batteries of Examples 1-10 at low temperatures are all lower than those of Comparative Examples 2 and 3, indicating that the film-forming additives provided in the embodiments of the present invention can better suppress the increase in impedance while improving the high-temperature cycle performance of the battery relative to existing film-forming additives such as vinylene carbonate and 1,3-propane sultone, thereby better balancing the high-temperature cycle performance and power performance of the battery.

[0126] Comparing Examples 4, 7-10 with Comparative Examples 2 and 3, it can be seen that compared with the existing film-forming additives vinylene carbonate and 1,3-propane sultone, the new film-forming additive provided by the embodiment of the present invention has a better effect in improving the high temperature cycle performance of the battery and can obtain a lower low temperature impedance. Comparing Examples 1-6, it can be seen that selecting a moderate value of the content of the film-forming additive in the electrolyte within the range of 0.1%-10% is conducive to taking into account both the high temperature cycle performance and low temperature impedance of the battery.

[0127] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. An electrolyte, characterized in that: The film-forming additive comprises an aminoborane and / or an aminoborane derivative; the aminoborane derivative comprises an aminoborane metal derivative, and the chemical formula of the aminoborane metal derivative is M(NH2BH3): n , where M is a metal and n is a positive integer equal to the chemical valence state of M.

2. The electrolyte according to claim 1, characterized in that The M is selected from at least one of Li, Na, K, Mg, Ca, and Al.

3. The electrolyte according to claim 1 or 2, characterized in that The aminoborane metal derivative includes at least one of LiNH2BH3, NaNH2BH3, KNH2BH3, Mg(NH2BH3)2, Ca(NH2BH3)2 and Al(NH2BH3)3.

4. The electrolyte according to claim 1, characterized in that The mass percentage of the aminoborane and / or aminoborane derivative in the electrolyte is 0.1%-10%.

5. The electrolyte according to claim 1, characterized in that The electrolyte further includes a lithium salt, and the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium tetrafluoroborate and lithium perchlorate.

6. The electrolyte according to claim 5, characterized in that The molar concentration of the lithium salt in the electrolyte is 0.1 mol / L-5 mol / L.

7. The electrolyte according to claim 1, characterized in that The electrolyte further includes a solvent, and the solvent includes at least one of a carbonate solvent, a carboxylate solvent, and an ether solvent.

8. The electrolyte according to claim 7, characterized in that The mass percentage of the solvent in the electrolyte is 10%-90%.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the electrolyte according to any one of claims 1 to 8.

10. An electrical device, characterized in that: The electrical equipment comprises the lithium-ion battery according to claim 9.

Citation Information

Patent Citations

  • Method for treating surface of hard carbon negative electrode of lithium battery

    CN108110232A

  • High-voltage electrolyte and battery comprising same

    CN114865061A

  • Electrolyte and battery

    CN115863740A

  • Lithium electrodeposition voltage reduction electrolyte and preparation method of lithium foil

    KR102363682B1

  • Anionic Polymers, Electrolytes Comprising the Same, and Methods of Manufacture Thereof

    US20200328470A1